Papillary Carcinoma of the Third Part of the Duodenum: A Case Report and Review of the Literature (Journal of Chittagong Medical College Teachers' Association, 2010)
Keywords: distal duodenal tumour; intractable vomiting; resectionDOI: 10.3329/jcmcta.v20i2.5630Journal of Chittagong Medical College Teachers' Association 2009: 20(2):56-59